2012
DOI: 10.1080/08870446.2011.626038
|View full text |Cite
|
Sign up to set email alerts
|

Mental contrasting of a dieting wish improves self-reported health behaviour

Abstract: Mentally contrasting a desired future with present reality standing in its way promotes commitment to feasible goals, whereas mentally indulging in a desired future does not. Dieting students (N = 134) reported their most important dieting wish that they deemed attainable within a 2-week period. Then, they were directed to mentally contrast or indulge in thoughts and images about the named dieting wish. A control condition was given no directions. Two weeks after the experiment, dieters retrospectively rated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…For example, teaching mental contrasting (vs. indulging) resulted in more effective time management and easier decision making in health care professionals (Oettingen, Mayer, & Brinkmann, 2010), better academic performance in disadvantaged schoolchildren (A. Gollwitzer, Oettingen, Kirby, Duckworth, & Mayer, 2011) and improved health behavior in dieting students (Johannessen, Oettingen, & Mayer, 2012).…”
Section: Research-article2013mentioning
confidence: 99%
“…For example, teaching mental contrasting (vs. indulging) resulted in more effective time management and easier decision making in health care professionals (Oettingen, Mayer, & Brinkmann, 2010), better academic performance in disadvantaged schoolchildren (A. Gollwitzer, Oettingen, Kirby, Duckworth, & Mayer, 2011) and improved health behavior in dieting students (Johannessen, Oettingen, & Mayer, 2012).…”
Section: Research-article2013mentioning
confidence: 99%
“…Oettingen et al ( 89 ) found that the mental contrasting intervention caused smokers who wanted to quit to take more immediate action toward quitting than subjects who underwent a control intervention. And for non-addicted subjects, Johannessen et al ( 99 ) found that dieters who performed the mental contrasting procedure were significantly more successful than control subjects at reducing their caloric intake over a 2-week period.…”
Section: Three Stages Of Self-controlmentioning
confidence: 99%
“…It is, of course, difficult in observational research to disentangle these (Johannessen, Oettingen, & Mayer, 2012), exercise goals (Sheeran et al, 2013), and a variety of goals in a depressed sample (Fritzsche et al, 2016). Dwelling only on the pleasures of attainment or only on the obstacles in its way tended to be counterproductive in leading participants to reach their goals (e.g., Oettingen, 1996), as, for instance, in their teachers' ratings of actual achievement (Oettingen et al, 2001).…”
Section: Facilitating Action Toward Goal-attainmentmentioning
confidence: 99%